2017
DOI: 10.1177/0958305x17722790
|View full text |Cite
|
Sign up to set email alerts
|

Back radiation versus CO2 as the cause of climate change

Abstract: Robust scientific evidence shows the sun angle controls water vapour content of the atmosphere, the main component of back radiation, as it cycles annually. Water vapour content measured as the ratio of the number of water molecules to CO2 molecules varies from 1:1 near the Poles to 97:1 in the Tropics. The effect of back radiation on Earth’s atmosphere is up to 200 times larger than that of CO2 and works in the opposite direction. Thus, if CO2 has any effect on atmospheric temperature and climate change we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…The purpose of this paper is to provide the details for constructing Figure 1 and to provide the evidence that the warming effect of CO 2 on the atmosphere is small enough to be negligible. This paper builds on the statement in Lightfoot et al, 2 "back radiation acts in opposition to the warming effect of the CO 2 " and provides new information. It provides the details necessary for the construction of Figure 1 that involve several scientific disciplines, such as, temperature and relative humidity records for Hamburg, Germany; the gas laws of Boyle and Charles/Gay-Lussac; psychrometric charts or programs; the back radiation measured at Hamburg; the concentration of CO 2 measured at Mauna Loa and the relative warming effect of various greenhouse gases (GHG) from Figure SPM.5.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The purpose of this paper is to provide the details for constructing Figure 1 and to provide the evidence that the warming effect of CO 2 on the atmosphere is small enough to be negligible. This paper builds on the statement in Lightfoot et al, 2 "back radiation acts in opposition to the warming effect of the CO 2 " and provides new information. It provides the details necessary for the construction of Figure 1 that involve several scientific disciplines, such as, temperature and relative humidity records for Hamburg, Germany; the gas laws of Boyle and Charles/Gay-Lussac; psychrometric charts or programs; the back radiation measured at Hamburg; the concentration of CO 2 measured at Mauna Loa and the relative warming effect of various greenhouse gases (GHG) from Figure SPM.5.…”
Section: Introductionmentioning
confidence: 80%
“…This value is above the average value for 2016 of approximately 404 ppmv. From the 407.9 baseline, the average July 1, concentration of CO 2 of 377.1 ppmv in dry air is calculated using the gas laws to adjust for pressure (elevation) and temperature (degrees, K) as in Equation 1: Similarly, the January concentration of CO 2 is calculated as in Equation 2: January 1 CO 2 concentration = 407.9 x (101230/101325) x (273/276) = 403.1 ppmv in dry air (2) Regardless of the concentration of CO 2 in the atmosphere, the gas laws always show a decrease in concentration with increased temperature and vice versa.…”
Section: Calculation Of the Concentration Of Co 2 In Dry Air At Hambu...mentioning
confidence: 99%
“…Water vapor causes approximately 91% at the Poles and 97.5% at the Tropics. The remainder of 2.5% to 9% is the sum of the warming by CO 2 , methane, nitrous oxide, and the remaining trace gases [9].…”
Section: Circlementioning
confidence: 99%
“…Many scholars [15,16,17,18,19,20] have claimed that global warming and climate change are associated with the amount of greenhouse gas emissions as measured by carbon dioxide equivalence. However, the literature also showed that there is no global consensus on this claim [21,22]. A report [23] mentioned that most of the leading scientific organizations around the world have issued public statements that endorse a position that 'climate warming trends over the past century are extremely likely due to human activities', and that the majority of actively publishing climate scientists (97%) agree that humans are causing climate change and global warming [24].…”
Section: Challenges To the Claims On The Causes Of Global Warming And...mentioning
confidence: 99%
“…The scholars noted that the concentration of water vapor in the atmosphere is controlled by the sun, and it in turn controls radiation, the temperature of the atmosphere, and climate. The study further mentioned that the effect of back radiation on earth's atmosphere is up to 200 times more than that of CO2 contributions, works opposite, and overrides the effect of CO2 to the extent that the contribution of CO2 to atmospheric temperature is negligible [22]. Regardless of the contradictions, it is still a commendable thing to make effort to improve the air quality in the environment where we work, live, and grow.…”
Section: Challenges To the Claims On The Causes Of Global Warming And...mentioning
confidence: 99%